2020
DOI: 10.1016/j.jsg.2020.104088
|View full text |Cite
|
Sign up to set email alerts
|

Growth of a thrust fault array in space and time: An example from the deep-water Niger delta

Abstract: The temporal and spatial evolution of thrust fault arrays is currently poorly understood, and marine fold and thrust belts at the toe of passive margin gravitational systems, imaged by commercial 3D seismic reflection datasets, afford a unique opportunity to investigate this problem in three dimensions. Using an extensive 3D seismic data set and age data, the total cumulative strain (shortening) and interval strain rates have been calculated for 11 thrust-related folds mapped in the toe-thrust region of the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(81 citation statements)
references
References 88 publications
2
79
0
Order By: Relevance
“…Thus, the main growth of gravity-driven structures started after ca. 9.5 Ma in the study area, nearly synchronous with adjacent regions (e.g., Pizzi et al, 2020). Within the late Miocene-to-present synkinematic Agbada Formation, several growth strata packages have been identified based on changing stratal geometries (Figure 4c), which were interpreted to represent different stages of structural growth evolution (Jolly et al, 2016;Krueger & Grant, 2011;Maloney et al, 2010).…”
Section: Geological Backgroundmentioning
confidence: 77%
See 2 more Smart Citations
“…Thus, the main growth of gravity-driven structures started after ca. 9.5 Ma in the study area, nearly synchronous with adjacent regions (e.g., Pizzi et al, 2020). Within the late Miocene-to-present synkinematic Agbada Formation, several growth strata packages have been identified based on changing stratal geometries (Figure 4c), which were interpreted to represent different stages of structural growth evolution (Jolly et al, 2016;Krueger & Grant, 2011;Maloney et al, 2010).…”
Section: Geological Backgroundmentioning
confidence: 77%
“…The Niger Delta basin is one of the classic shale tectonic province in the world where deepwater gravitational systems are widely developed and studied (e.g., Cohen & McClay, 1996; Corredor et al., 2005; Damuth, 1994; Jolly et al., 2017, 2016; Morley & Guerin, 1996; Pizzi et al., 2020; Rouby et al., 2011; Wu & Bally, 2000; Wu et al., 2015). Previous studies found that the structural development of deepwater gravitational systems is closely related to deformation within the ductile substrate, composed of undercompacted and overpressured mobile shales (e.g., Bonini, 2003; Cohen & McClay, 1996; Deville et al., 2006; Duerto & McClay, 2011; Fillon et al., 2013; Hansberry et al., 2014; Morley, 2003; Morley & Guerin, 1996; Morley et al., 2011, 2017, 1998; Wu & Bally, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several of the most laterally persistent folds are marked by seabed scarps at their crests and actively deform the seabed. The structural and tectonic evolution of these structures have been documented by Jolly et al (2016) and Pizzi et al (2020): measurements of shortening and cumulative strain were calculated across four of the major thrust folds generating topographic relief. Line-length balancing was F I G U R E 3 (a) Three-dimensional (3-D) bathymetric map of the seabed showing the geomorphic expression of the two modern channels (black dashed lines), and structures that occur at, or near, the seabed (labelled a-g).…”
Section: Study Areamentioning
confidence: 99%
“…layer thickness and bed length are conserved during deformation). Recent work in the southern lobe of the Niger Delta shows that this approach is associated with measurement error of ±15% (Pizzi et al, 2020).…”
Section: Distribution Of Strain and Structural Upliftmentioning
confidence: 99%